Sail away to a safe harbor? Covid-19 vaccinations and the volatility of travel and leisure companies - Ender Demir; Renatas Kizys; Wael Rouatbi; Adam Zaremba (Journal of Risk and Financial Management, 2022)
This paper examines the impact of vaccination programs on the stock market volatility of the travel and leisure sector. Using daily data from 56 countries over the period from January 2020 to March 2021, we find that vaccination leads to a decrease in the investment risk of travel and leisure companies. Vaccination results in a decrease in the volatility of stock prices of travel and leisure companies. The drop in volatility is robust to many alternative estimation techniques, different volatility measures, and various proxies for vaccinations. Moreover, this effect cannot be explained by an array of control variables; this includes the pandemic itself and both the containment and closure policies that followed. Furthermore, the beneficial role of vaccinations is relatively stronger in emerging markets than in developed ones.
Keywords: 650; COVID-19; pandemic; stock market volatility; travel and leisure; vaccinations